Addressing clinical equipoise for hearing devices: the qualitative COACH (q-COACH) study protocol for Australian stakeholder involvement in the design of a randomised controlled trial. Issue 9 (8th September 2019) - Rapport, Frances; Auton, Emilie; Warren, Chris; Braithwaite, Jeffrey
Abstract : Introduction: Hearing loss is a common chronic problem which can be effectively managed with hearing devices. At present, only a limited number of people with hearing loss use hearing aids (HAs) and cochlear implants (CIs) to improve hearing and sound quality and enhance quality of life. Clinical equipoise, by which we mean healthcare professional uncertainty about which treatment options are the most efficacious due to the lack of evidence-based information, can lead to inconsistent and poorly informed referral processes for hearing devices. A randomised controlled trial (RCT) that offers high-quality, generalisable information is needed to clarify which hearing device (HA or CI) is more suitable for different degrees of hearing loss and for which kinds of patients. Qualitative research can improve this RCT, by gathering the information on patient and provider perspectives, attitudes and values, which can inform design, conduct and information dissemination, either during preparatory stages of an intervention, or as a fully integrated methodology. The Comparison of Outcomes with hearing Aids and Cochlear implants in adults with moderately severe-to-profound bilateral sensorineural Hearing loss (COACH) study is being planned as an RCT with a qualitative arm (the qualitative COACH study, q-COACH), acting as a pretrial intervention examining views of HAs, CIs, equipoise and the impetus for an RCT of this nature. Methods and analysis: The q-COACH study involves semistructured interviews and a demographic questionnaire which will be collected from four participant cohorts: General Practitioners (GPs) and Ear, Nose and Throat Surgeons (ENTs); audiologists; adult HA users and their support networks. Data will be analysed thematically and through descriptive statistics. Ethics and dissemination: Macquarie University Human Research Ethics Committee, Australia, granted ethical approval (no. 5201833514848). Peer-reviewed journal articles, research conferences and a final report will present study findings.